2022
DOI: 10.1155/2022/3092941
|View full text |Cite|
|
Sign up to set email alerts
|

Preparation and Energy Storage Performance of Perovskite Luminescent Materials by an Electrochemiluminescence Method

Abstract: In recent years, metal halide perovskites have become attractive photosensitive materials due to their excellent optoelectronic properties. Due to its good characteristics, perovskites are used in solar photovoltaic power generation, light-emitting diodes, photodetectors, photocatalysis, and sensors and many other fields. Considering the wide application of perovskites and the study of potential bifunctional devices, the application of perovskites in energy storage devices is relatively small, and a small numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This new type of semiconductor material has a broad range of applications in the fields of photovoltaics and optoelectronics [8][9][10]. All-inorganic cesium lead halide perovskites (CsPbX 3 , X = Cl, Br, I) have been shown to be highly luminescent, with narrow emission linewidths, high chromatogram purity and a wide range of emission wavelengths across all visible regions [11][12][13]. It can be widely used in the field of flexible photoelectric displays.…”
Section: Introductionmentioning
confidence: 99%
“…This new type of semiconductor material has a broad range of applications in the fields of photovoltaics and optoelectronics [8][9][10]. All-inorganic cesium lead halide perovskites (CsPbX 3 , X = Cl, Br, I) have been shown to be highly luminescent, with narrow emission linewidths, high chromatogram purity and a wide range of emission wavelengths across all visible regions [11][12][13]. It can be widely used in the field of flexible photoelectric displays.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%